Public and private hospitals in Cameroon : service quality and patients' choice of hospitals - Shu, Cletus Ambe (Eastern Mediterranean University (EMU), 2010)
ABSTRACT: As many governments struggle to find the necessary resources to invest in the public healthcare system, private healthcare providers are becoming an important alternative for patients. Service quality has become a very important concept in healthcare. However, there is a paucity of research conducted in this area in African countries. This study tries to identify important factors customers consider when choosing a healthcare provider. It also applies the SERVQUAL model to compare the level of service quality provided by public and private hospitals in the Northwest Region of Cameroon. Furthermore, it looks at customers overall level of satisfaction with the services, their repurchase intentions and their recommendation of the service to others. A total of 244 hospital users in Cameroon responded to a 3 part questionnaire in English. The findings of the study revealed that generally, there was no difference between public and private hospitals users in terms of selection factors. Customers’ expectations from both types of hospitals were low. A significant relationship was found between service quality dimensions and overall customer satisfaction. A positive significant relationship also existed between overall customers’ satisfaction, loyalty and positive word of mouth. There is overall dissatisfaction with both customers who can and those who cannot afford healthcare in Cameroon. This is a surprise finding especially for private healthcare providers who need to improve the quality of service they offer to the elite group of customers who are willing to pay for it. As for the public sector, the government needs to invest more resources towards improving the services of public hospitals. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Birçok devlet sağlık sektörüne gereken ilgi ve kaynak aktarımını sağlayamamaktadır. Dolayısıyla özel sağlık kuruluşlarının önemi gün geçtikce artmakta, özellikle bu hizmetleri alabilecek durumda olan müşteriler için. Servis kalite anlayışı sağlık sektöründe önemli bir rol oynamaktadır. Bu alanda birçok çalışma yapılmasına rağmen, Afrika ülkelerindeki sağlık alanında yapılan çalışmalar kısıtlıdır. Bu tez Kamerun’un kuzeybatısındaki kamu ve özel hastanelerdeki müşterileri kıyaslayarak hastane seçim kıstasları, servis kalitesi ve müşteri memnuniyeti arasındaki ilişkiyi sorgulamaktadır. Ayrıca müşteri memnuniyeti ile hizmetden tekrar faydalanma eğilimi ve başkalarına tavsiye arasındaki ilişki incelenmektedir. İngilizce hazırlanan, üç bölümlük bir ankete toplam 224 kişi cevap vermiştir. Araştırmanın sonunda, kamu ve özel hastane müşterileri hastane seçim kıstasları açısından bir farklılık göstermemektedir. Müşterilerin hem özel hem de kamu hastanelerinden beklentileri genellikle düşüktür. Hem kamu hem de özel hastane müşterilerinin memnuniyet ölçeği puanlarının ortalamanın çok altında olduğu görülmektedir. Çalışmada ayrıca kapsamlı müşteri memnuniyeti, hizmetden tekrar faydalanma eğilimi ve hizmeti başkalarına önerme eğilimi arasında tutarlı ve pozitif bir ilişki tespit edilmiştir. Sonuç olarak, hem özel hem de kamu hastane müşterisi aldığı hizmetden genel olarak memnun değildir. Kamerun ‘daki kamu hastane yöneticileri kısıtlı kaynaklarını daha verimli kullanarak servis hizmet kalitesini yükseltmeye çalışmalı ve devlet bu alana daha çok kaynak ayırmalıdır. Diğer yandan, özel sektör yöneticileri fakirliğin yaygın olduğu bir ülkede paralı ve elit müşterilerini tutmak istiyorlarsa müşterilerinin ödediği bedelin karşılığını vermek zorundadırlar.
MBA in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2010. Supervisor: Assist. Prof. Dr. Salime Mehtap Smadi
Keywords: Health Care - Health Facilities - Hospitals - Service Quality - Cameroon; Health services Quality; Selection Factors - SEVQUAL - Customer Satisfaction - Public and Private Hospitals - Cameroon